Study Of Physiological Characteristics Of Sorghum Seeds (Sorghum Bicolor L.) That Have Been Invigorated - Yopa Dwi Mutia (JERAMI : Indonesian Journal of Crop Science, 2020)
The limiting factor affecting the production of sorghum in Indonesia is the rapid decline of sorghum seed vigor and viability. One way of restoring vigor and viability is hydration-dehydration. This study aimed to know that invigoration with the hydration-dehydration method can improve the quality of physiological sorghum seed and to determine the most appropriate conditions to use. This experiment used a completely randomized design (CRD) with 3 treatments and 4 replicates and was conducted at the Laboratory of Seed Science and Technology, Andalas University from January until March 2019. The treatment in these trials are: A = not hydrated-dehydrated seeds (control), B = Hydration for 1 hour and dehydration for 6 hours at the temperature 400C, C = high-quality seeds. The data were analyzed using the F test at the 5% significance level. Significant differences were further analyzed using an Honestly Significant Difference (HSD) test also at the 5% level. The results showed that hydration-dehydration can increase the vigor and viability of sorghum seeds from 56% to 70,5% and 55% to 75%.